Correlation of Demographics, Healthcare Availability, and COVID-19 Outcome: Indonesian Ecological Study - Wirawan, Gede Benny Setia; Januraga, Pande Putu (Frontiers in Public Health, 2021)
Objective: To analyze the correlation between demographic and healthcare availability indicators with COVID-19 outcome among Indonesian provinces. Methods: We employed ecological study design to study correlation between demographic, healthcare availability and COVID-19 indicators. Demographic and healthcare indicators were obtained from Indonesian Health Profile of 2019 by Ministry of Health while COVID-19 indicators were obtained from Indonesian COVID-19 website in August 31st 2020. Non-parametric correlation and multivariate regression analyses were conducted with IBM SPSS 23.0. Results: We found number of confirmed case and case growth to be significantly correlated with demographic indicators, especially with distribution of age groups. Confirmed case and case growth was significantly correlated (p<0.05) with population density (correlation coefficient of 0.461 and 0.491) and proportion of young people (-0.377; -0.394). Incidence and incidence growth were correlated with ratios of GP (0.426; 0.534), hospital (0.376; 0.431), primary care clinic (0.423; 0.424) and hospital beds (0.472; 0.599) per capita. For mortality, case fatality rate (CFR) was correlated with population density (0.390) whereas mortality rate was correlated with ratio of hospital beds (0.387). Multivariate analyses found confirmed case independently associated with population density (β of 0.638) and demographic structure (-0.289). Case growth was independently associated with density (0.763). Incidence growth was independently associated with hospital bed ratio (0.486). Conclusion: Pre-existing inequality of healthcare availability correlates with current reported incidence and mortality rate of COVID-19. Lack of healthcare availability in some provinces may have resulted in artificially low number of suspects being diagnosed, lower demands for COVID-19 tests, and eventually lower case-finding.